2008
DOI: 10.1038/ncb1764
|View full text |Cite
|
Sign up to set email alerts
|

A ribosomal protein L23-nucleophosmin circuit coordinates Miz1 function with cell growth

Abstract: The Myc-associated zinc-finger protein, Miz1, is a negative regulator of cell proliferation and induces expression of the cell-cycle inhibitors p15(Ink4b) and p21(Cip1). Here we identify the ribosomal protein L23 as a negative regulator of Miz1-dependent transactivation. L23 exerts this function by retaining nucleophosmin, an essential co-activator of Miz1 required for Miz1-induced cell-cycle arrest, in the nucleolus. Mutant forms of nucleophosmin found in acute myeloid leukaemia fail to co-activate Miz1 and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 43 publications
5
104
0
Order By: Relevance
“…93 Thus, NPM1 mutant-mediated enhanced proliferative activity (by increasing c-Myc protein levels) may be a potential player in leukaemogenesis. 94 Wanzel et al 30 found that the NPM1 leukaemic mutant interacted with the Myc-associated zinc-finger protein Miz1, dislocating it into cytoplasm. When complexed with the NPM1 mutant in cytoplasm, Miz1 no longer exerted its physiological action of negatively regulating cell proliferation by inducing expression of cell-cycle inhibitors p15 and p21.…”
Section: Delocalization Of Proteins Involved In Control Of C-myc and mentioning
confidence: 99%
See 2 more Smart Citations
“…93 Thus, NPM1 mutant-mediated enhanced proliferative activity (by increasing c-Myc protein levels) may be a potential player in leukaemogenesis. 94 Wanzel et al 30 found that the NPM1 leukaemic mutant interacted with the Myc-associated zinc-finger protein Miz1, dislocating it into cytoplasm. When complexed with the NPM1 mutant in cytoplasm, Miz1 no longer exerted its physiological action of negatively regulating cell proliferation by inducing expression of cell-cycle inhibitors p15 and p21.…”
Section: Delocalization Of Proteins Involved In Control Of C-myc and mentioning
confidence: 99%
“…As an example, NPM1 mutants dislocate HEXIM1 into cytoplasm and the consequent increase in P-TEFb-dependent transcription was advocated as a potential target for P-TEFb inhibitors, such as flavopiridol and CYC202. 120 The current list of molecules that are mislocalized by the NPM1 mutants 25,30,78,79,89,91,92 may be only the 'tip of the iceberg' and the use of mass spectrometry and immunohistochemistry is expected to identify other target proteins and possibly help defining the functional significance of their dislocation. Better understanding of the structural bases of NPM1 heterodimerization with other proteins could help development of molecules able to target this interface, thus preventing mutated NPM1 from delocalizing, and inactivating, potential tumour suppressors.…”
Section: Altered Traffic Of Nucleophosmin In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…Many POZ-domain proteins are transcriptional repressors that localize as insoluble complexes in specific subnuclear compartments. In contrast, free MIZ-1 is a strong transactivator that uses a typical acidic domain for activation of its target genes, using both p300 and Npm1 (nucleophosmin) as coactivators (Staller et al 2001;Wanzel et al 2008). Most likely, therefore, the physiological function of MIZ-1 during normal development is to activate a set of target genes; unpublished work from our laboratory shows that direct target genes of MIZ-1 include many genes involved in autophagy and membrane transport.…”
mentioning
confidence: 99%
“…In the network of signaling transduction, the positive feedback loop regulation plays important roles in determining the progressive nature of malignant cancer cells including cell proliferation [2][3][4][5] . Extracellular signal-regulated kinase 1/2 (ERK1/2), a major cellular proliferation signaling pathway, is involved in many positive feedback loops.…”
Section: Introductionmentioning
confidence: 99%